Constituents of the zingiberaceae. XI structures of (+)-(1R, 2S, 3R, 4S)-2-Benzoyloxy- methylcyclohex-5-ene-l, 2, 3, 4-tetrol 4-Benzoate [(+)-Zeylenol] and (+)1R, 2R, 4R, 5S, 6R, 7R)- 4-benzoyloxymethyl-3, 8-dioxatricyclo- [5.1.0.02, 4]octane-5, 6-diol 5-Acetate 6-benzoate (boesenboxide) isolated from a new boesenbergia species - Pittaya Tuntiwachwuttikul (2018)
A new Boesenbergia species (Zingiberaceae) has been found to contain (+)- (lR, 2S, 3R, 4S)-2-benzoyloxymethylcyclohex-5-ene-l, 2, 3, 4-tetrol 4-benzoate [(+)-zeylenol] (2) and the crotepoxide-related substance, (+)-(1R, 2R, 4R, 5S, 6R, 7R)-4-benzoyloxymethyl-3, 8- dioxatricyclo[5.1.0.0 2, 4 ]octane-5, 6-diol 5-acetate 6-benzoate (boesenboxide) (8). The structure (8) was determined by spectroscopic, chemical, and X-ray crystallographic studies. Boesenboxide forms monoclinic crystals P2 1 , a 12·722(2), b 5·230(1), c 16·139(3) Å, β 106·57(1)° the crystal structure was refined to a residual of 0·029 for 1281 independent observed reflections. © 1987 ASEG.